Child-Centered Evaluation: Broadening the Child/Designer Dyad. (9th July 2008) - Pardo, Sofia; Howard, Steve; Vetere, Frank
Abstract : Some settings challenge a literal interpretation of user-centered design orthodoxy; that design is best done for a user, by designing with that user. We explore the value that a copresent proxy and interpreter can bring to certain hard-to-reach or difficult-to-interpret situations; in this case the evaluation of educational software intended to be used by children. We discuss the effect that introducing a teacher had on the results of the evaluation and conclude that adding an expert-based component to evaluations increased its diagnostic power.